Development mode of reverse fault‐associated fractures in deep tight sandstones: A case study in Xinchang Gas Field, Sichuan Basin, China. (28th January 2021) - Xie, Runcheng; Zhou, Wen; Xiang, Mingliang; Yin, Shuai; Zhang, Mengyuan; Wang, Yongfei; Chen, Jian
Abstract : Evaluation of natural fractures is the key issue of the prediction of sweet spots in deep tight sandstones. In this article, taking the tight gas sandstone reservoir of the Xu 2 Member (second member of the Upper Triassic Xujiahe Formation) in Xinchang Gas Field, West Sichuan Depression as an example, we systematically studied the characteristics, formation periods, influencing factors, and developmental mode of fractures using testing results of cores, thin sections, rock mechanics, isotopes, fluid inclusions, and the structural curvature simulation method. The results show that the Xu 2 Member mainly develops vertical and high‐angle fractures. The fractures are highly effective and mainly developed in medium‐fine‐grained sandstone. The secondary minerals in the fractures have multi‐stage filling processes. The fluid inclusions are mainly gas–liquid two‐phase brine inclusions (secondary inclusions), and with the same crystal, the temperature difference between the brine inclusion and the organic inclusion is 23.7°C. Carbon and oxygen stable isotope tests show that calcite has two mixing stages. In the end, the formation periods of the fractures in the Xu 2 Member were divided into five stages. The influencing factors of fractures in the Xu 2 Member include lithology, fault, layer thickness, and structural deformation. According to geomechanical analysis, we finally established the development mode of reverse fault‐associated fractures in the Xu 2 Member. Abstract : Development mode of reverse fault‐associated fractures.